Pemanfaatan Budidaya Lebah Madu Sebagai Media Terapi Guna Peningkatan Ekonomi Masyarakat Kampung Baru - Dhita Adriani Rangkuti; Mas Intan Purba; Jamaluddin Jamaluddin; Muhammad Agung Anggoro; Melkyory Andronicus (Universitas Pahlawan Tuanku Tambusai, 2023)
This community service activity aims to provide training on entrepreneurship in terms of seeing business opportunities that exist in beekeeping, especially honey beekeeping in the hope of helping the welfare of the new village community by opening innovative and useful businesses. By using the method of observation, outreach and implementation of activities. The result of this activity was that the participants received training and an understanding of beekeeping which has many benefits, one of which is not only as a therapeutic medium but also has the potential to generate promising business opportunities so that 16 out of 25 participants felt interested in running this business.